Differential impact of two major polychaete guilds on microbial communities in marine sediments: a microcosm study - Deng, Longhui; Fiskal, Annika; Bölsterli, Damian; Meier, Dimitri; Meile, Christof; Lever, Mark Alexander (Frontiers in Marine Science, 2023)
Even though sediment macrofauna are widespread in the global seafloor, the influence of these fauna on microbial communities that drive sediment biogeochemical cycles remains poorly understood. According to recent field investigations, macrofaunal activities control bacterial and archaeal community structure in surface sediments, but the inferred mechanisms have not been experimentally verified. Here we use laboratory microcosms to investigate how activities of two major polychaete guilds, the lugworms, represented by Abarenicola pacifica, and the clamworms, represented by Nereis vexillosa, influence microbial communities in coastal sediments. A. pacifica treatments show >tenfold increases in microbial cell-specific consumption rates of oxygen and nitrate, largely due to the strong ventilation activity. While ventilation resulted in clearly elevated percentages of nitrifying archaea (Nitrosopumilus spp.) in surface sediments, it only minorly affects bacterial community. By comparison, reworking – mainly by deposit-feeding of A. pacifica – had a more pronounced impact on microorganismal communities, significantly driving down abundances of Bacteria and Archaea. Within the Bacteria, lineages that have been linked to the degradation of microalgal detritus (e.g., Flavobacteriaceae and Rhodobacteraceae), were especially affected, consistent with the previously reported selective feeding of A. pacifica on microalgal detritus. In contrast, N. vexillosa, which is not a deposit feeder, did not significantly influence microbial abundances or microbial community structure. This species also only had a relatively minor impact on rates of oxygen and nitrogen cycling, presumably because porewater exchanges during burrow ventilation by this species are mainly restricted to sediments immediately surrounding the burrows. Collectively our analyses demonstrate that macrofauna with distinct bioturbation modes differ greatly in their impacts on microbial community structure and microbial metabolism in marine sediments.